Pengaruh Penggunaan Komposisi Media Tanam terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium cepa L.) - Susilawati Susilawati; Muhammad Ammar; Mu’arif Mu’arif (Seminar Nasional Lahan Suboptimal, 2018)
Susilawati et al, 2019.The Effect of Using Growing Media Composition on Growth and Yield of Shallot (Allium cepa L.). pp. 93-102.The aimed of research was to study the effect of using growing media composition on growth and yield of shallot (Allium cepa L.). Research was conducted from February until April 2017. Design used in this study was randomized block design (RBD) with 9 treatments and 3 replications. The treatments was A0 = Control (90% soil : 10% chicken manure), A1 = 80% soil : 20% cow manure, A2 : 70% soil : 30% cow manure, A3 = 60%  soil : 40% cow manure, A4 = 50% soil : 50% cow manure , A5 = 80% soil : 20% husk charcoal, A6 = 70% soil : 30% husk charcoal, A7 = 60% soil : 40%  husk charcoal, A8 = 50% soil : 50 husk charcoal. The results showed that the use of planting media composition of 60% soil : 40% of cow manure can improve the growth and yield of shallot plants better. This is consistent with plant height variables, number of leaves, number of tillers, number of tubers, fresh weight of tubers, and dry weight of tubers. The highest dry weight yield was found in the composition of 60% soil : 40% of cow manure with an average yield of 84.36 g per hill.